BEYOND COLOUR: THE EVOLUTION OF MEANING REPRESENTATION - Platonova, Marina; Iljinska, Larisa (Vertimo studijos, 2017)
The present paper is only a small part of the investigation we have performed into the evolution of how the meaning of colour is represented in contemporary LSP texts. The English language is undergoing a process of change characterized by a tendency towards the extension of the meaning of lexical units. This tendency can be observed in the semantic field of colour, which is a significant component of the cognitive models that enable both an understanding and representation of reality. Having studied multiple sources and analyzed numerous examples illustrating the historical evolution of this phenomenon, we aim to demonstrate both the complex, multifaceted nature of colour terms and their possible application in the designation of concepts and the formation of new terms. Within the scope of this paper, we have investigated the mechanisms of how contemporary colour-based terms are formed with the additional aim of broadening the perception of colour term applications.